Análise do impacto do sistema de cotas nas Universidades Públicas Paulistas frente a egressos do Ensino Médio de uma instituição privada - Cabral, Marcelo Veraldi (2019)
This research aims to present a sociological study based on empirical database research concerning senior high school students of a private school. Our goal is to point out this specific group’s perspective under a transitional educational context, specifically when the quotas for those who do not declare themselves white and for those who have finished high school in public institutions. Those changes are connected to the admission processes in public universities, thus impacting the route taken by middle-class students, who still aim to study at public universities in São Paulo, mainly as a status valuable for themselves as social individuals. Pierre Bourdieu, Décio Saes are the authors used to study social classes; David Harvey, among others, have been used to study Neoliberalists politics impacts, thus bringing the bases to, during this work, analyzing the behavior of middle-class individuals under the admission processes of universities. The quotas policies and new admission processes on the state colleges of São Paulo, brought by the usage of ENEM (high school national exam) grades, SISU (national unified selection system, concerning federal and state colleges), have promoted both middle-class behavior changes and also middle-class family expectations, as it could be seen on the interviews. Some hypotheses are brought, being its main the entrance of an important university something which will differ the students as individuals under their social status, thus at marketplace. The research has brought as results the understanding that the most valuable diplomas (symbolic capital) still belong to the group of public universities. Another observation was that tolerance was shown by the interviewees, who agree to the quotas policy. After our analysis, the youth group researched are unequal to the racial quotas on the admission processes